Analisis Kinerja Keuangan Bank Umum Syariah di Bursa Efek Indonesia: Perspektif Pendekatan Kontemporer - Muh Rifkiadi Nasir; Muryani Arsal; Sahrullah (Scimadly Publishing, 2026)
This study analyzes the performance of Islamic Commercial Banks listed on the Indonesia Stock Exchange (IDX) for the 2022–2025 period using the contemporary Maqashid Sharia Index (MSI) approach. Traditionally, banking health assessments have focused mainly on profitability and conventional financial ratios. In contrast, the existence of Islamic financial institutions demands a balance between business achievements and the holistic realization of Sharia objectives. This study employs a quantitative descriptive method by evaluating the annual reports of four sample banks PT Bank Syariah Indonesia Tbk (BRIS), PT Bank BTPN Syariah Tbk (BTPS), PT Bank Panin Dubai Syariah Tbk (PNBS), and PT Bank Aladin Syariah Tbk (BANK), based on the three main dimensions of Maqashid Sharia: Tahdzib al-Fard (individual education and human resource development), Iqamah al-'Adl (upholding justice and governance), and Jalb al-Maslahah (creation of public interest and societal welfare). The results show that each bank exhibits diverse performance characteristics; BRIS excels in scale and comprehensive stability, BTPS is strong in microeconomic empowerment, and PNBS and BANK focus on enhancing competitiveness through digital innovation. Overall, the use of the Maqashid Sharia Index provides a more comprehensive performance evaluation by integrating financial aspects with the level of Sharia compliance and tangible contributions to public welfare.